Guide for new supervisors of honours and coursework dissertation students. - Robert, Lynne D. (Australia. Office for Learning and Teaching, 2015)
This is a guide that provides generic information for new supervisors of Undergraduate, Honours and Masters by coursework programs. The guide is structured to provide information that supervisors may find useful at various stages of the dissertation supervision process. For each stage of the dissertation supervision process an introductory overview is provided, and this is supplemented (where available) with checklists, best practice advice and possible tools. The information provided in this guide may need to be modified or extended to suit the requirements of your discipline or level of dissertation. [Introduction, ed]